Variability of Suspended Particle Properties Using Optical Measurements Within the Columbia River Estuary. Issue 9 (6th September 2018) - Tao, Jing; Hill, Paul S.; Boss, Emmanuel S.; Milligan, Timothy G.
Abstract: Optical properties are used to understand the spatial and temporal variability of particle properties and distribution within the Columbia River Estuary, especially in the salinity transition zone and in the estuarine turbidity maximum region. Observations of optical properties in the Columbia River Estuary are consistent with the established model that the river water brings more organic, smaller particles into the estuary, where they flocculate and settle into the salt wedge seaward of the density front. Large tidal currents resuspend mineral‐rich, larger aggregates from the seabed, which accumulate at the density front. Optical proxies for particle size (beam attenuation exponent γ and backscattering exponent γ b b ) are compared to conventional measurements. The γ and γ b b are different to the expected trend with Sauter mean diameter D s of suspended particles from low‐ to medium‐salinity waters (LMW). D s increases in the LMW as does the γ derived from a WET Labs ac‐9, which indicates that the particle population dominating the ac‐9 is decreasing in size. The most likely explanation is that flocculation acting at LMW transfers mass preferentially from medium‐sized particles to large‐sized particles that are out of the size range to which the ac‐9 is most sensitive; γ b b shows no trend in the LMW. Since γ b b is a proxy of proportion of fine particles versus large flocs, the variation of γ b b may be insensitive to changes in the medium‐sized particles. The overall results demonstrate that γ b b is a reliable proxy for changes in particle size in a stratified environment. Plain Language Summary: Suspended particles delivered by rivers affect water quality in estuaries, so effective and economical monitoring of the variability of particles is particularly important in environmental management. Direct measurements of suspended particle size, concentration, and composition from water samples require substantial time and labor, which has driven efforts to develop indirect, yet accurate, alternative measurements of particle properties. In this study, we used optical instruments to measure particle variability within the Columbia River Estuary. The observations demonstrate that the river water delivered smaller, organic particles to the estuary, where they aggregated with one another and deposited to the seafloor. Large tidal currents resuspended mineral‐rich, larger aggregates from the seafloor, and these aggregates accumulated in the region where river waters encountered coastal ocean waters that flowed into the estuary. We observed that optical measurements related to particle size were different from the expected trend in the transition zone between fresh, river water and salty, coastal water. This unexpected trend requires more study, but we propose that it was caused by preferential aggregation of medium‐sized organic‐rich particles into large particles. This process would affect the processing of carbon, nutrients, and contaminants in estuaries. Key Points: Optical properties provide a good representation of particle dynamics in the Columbia River Estuary Variations of alternative optical proxies for particle size are different to the expected trend at salinity transition zone Observations are consistent with a model of preferential flocculation of medium‐sized particles